The effects of Instagram ads and Facebook ads on brand awareness at Sthala, a Tribute Portfolio Hotel, Ubud, Bali - I Putu Weda Wiguna; Kadek Jemmy Waciko; Wayan Suryathi (Priviet Social Sciences Journal, 2026)
This study examines how perceived Instagram Ads and Facebook Ads exposure is associated with brand awareness of Sthala, a Tribute Portfolio Hotel, Ubud, Bali. A cross-sectional quantitative survey was conducted with 100 active Instagram and Facebook users selected through purposive sampling. Exposure was treated as respondents' self-reported recognition of the hotel's official promotional content rather than as platform-verified impressions. The questionnaire measured Instagram Ads, Facebook Ads, and brand awareness using five-point Likert items. The data were analyzed using validity and reliability tests, classical-assumption diagnostics, multiple linear regression, t-tests, an F-test, and the coefficient of determination. Instagram Ads showed a positive association with brand awareness (B = 0.372, β = 0.504, t = 6.092, p < .001), while Facebook Ads also showed a positive association (B = 0.297, β = 0.368, t = 4.444, p < .001). The model was significant, F(2, 97) = 85.975, p < .001, and explained 63.9% of the variance in brand awareness (R² = .639; adjusted R² = .632). Instagram Ads had the stronger standardized association. The study contributes a platform-specific comparison in a post-pandemic Bali hospitality setting and shows that visually oriented Instagram advertising and information-rich Facebook advertising can play complementary roles in strengthening hotel brand awareness. Because the study used cross-sectional self-report data from one hotel, the findings should be interpreted as associations rather than definitive causal effects.